Myocardial infarction in a patient with left ventricular noncompaction: a case report - Toufan, Mehrnoush (Dove Medical Press, 2012)
We describe a 73-year-old male patient with left ventricular noncompaction (LVNC) who was diagnosed with acute myocardial infarction (MI), three-vessel coronary artery disease, a fresh intraventricular thrombus, and mitral regurgitation. He was treated with full anticoagulant therapy, coronary artery bypass grafting, and mitral valve repair. This case adds to a small but growing literature showing association between LVNC and MI and/or coronary artery disease. We suggest that patients with LVNC could be considered at heightened risk for MI, and the two conditions might have a common genetic underpinning in some cases.